2012
DOI: 10.1002/cbic.201200633
|View full text |Cite
|
Sign up to set email alerts
|

A Domain of RubC1 of Rubradirin Biosynthesis Can Functionally Replace MbtH‐Like Proteins in Tyrosine Adenylation

Abstract: Master of your domain: A domain of the bifunctional enzyme RubC1 catalyzes the adenylation of tyrosine. This domain can be activated not only by MbtH-like proteins but also by another domain of RubC1 that has no similarity to MbtH-like proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…32 They seem to have high specicity for their particular A domain partners, but some examples of weak complementarity are reported. 33 The roles of MbtH-like proteins have been explored in a variety of biochemical and structural studies, 17,[33][34][35][36][37][38][39][40][41][42][43][44][45][46] but their exact functions and mechanisms of action still remain elusive.…”
Section: Adenylation Domain Core Signature Sequences and Structuresmentioning
confidence: 99%
“…32 They seem to have high specicity for their particular A domain partners, but some examples of weak complementarity are reported. 33 The roles of MbtH-like proteins have been explored in a variety of biochemical and structural studies, 17,[33][34][35][36][37][38][39][40][41][42][43][44][45][46] but their exact functions and mechanisms of action still remain elusive.…”
Section: Adenylation Domain Core Signature Sequences and Structuresmentioning
confidence: 99%
“…The full genome of S. sibiricum is not yet available, and hence whether there is an MLP‐encoding gene elsewhere in the genome is not known. In some examples, MLPs from certain hosts can replace the function of MLPs from native sources . For instance, the MLPs CloY and SimY coded by gene clusters from different Streptomyces species responsible for the biosynthesis of chlorobiocin and simocyclinone D8, respectively, can activate both of the tyrosine adenylases that initiate the assembly of a common aminocoumarin moiety .…”
Section: Methodsmentioning
confidence: 99%
“…While most MLPs are independent proteins, some are covalently joined to adenylation domains in multidomain proteins. Additional adenylation domain activators have also been observed in other multidomain NRPSs [40,41]. Finally, other domains have been identified that serve as scaffolds for the interaction with additional catalytic partners.…”
Section: Combining Nrps Domains To Build a Modulementioning
confidence: 99%